(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper analyzes the bronze head of cloak pin discovered at Monte Zara- Is Obias (Monastir-CA). Stratigraphic association and morphologic comparison contextualize the evidence during the frequentation of the site in II Iron Age.